Treatment With Tetrahydrobiopterin Overcomes Brain Death–Associated Injury in a Murine Model of Pancreas Transplantation - Oberhuber, R. (Am J Transplant, 2015)
Brain death (BD) has been associated with an immunological priming of donor organs and is thought to exacerbate ischemia reperfusion injury (IRI). Recently, we showed that the essential nitric oxide synthase co‐factor tetrahydrobiopterin (BH4) abrogates IRI following experimental pancreas transplantation. We therefore studied the effects of BD in a murine model of syngeneic pancreas transplantation and tested the therapeutic potential of BH4 treatment. Compared with sham‐operated controls, donor BD resulted in intragraft inflammation reflected by induced IL‐1ß, IL‐6, VCAM‐1, and P‐selectin mRNA expression levels and impaired microcirculation after reperfusion (p < 0.05), whereas pretreatment of the BD donor with BH4 significantly improved microcirculation after reperfusion (p < 0.05). Moreover, BD had a devastating impact on cell viability, whereas BH4‐treated grafts showed a significantly higher percentage of viable cells (p < 0.001). Early parenchymal damage in pancreatic grafts was significantly more pronounced in organs from BD donors than from sham or non‐BD donors (p < 0.05), but BH4 pretreatment significantly ameliorated necrotic lesions in BD organs (p < 0.05). Pretreatment of the BD donor with BH4 resulted in significant recipient survival (p < 0.05). Our data provide novel insights into the impact of BD on pancreatic isografts, further demonstrating the potential of donor pretreatment strategies including BH4 for preventing BD‐associated injury after transplantation.